2020
DOI: 10.1101/2020.08.16.253294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural defects caused by Acrodermatitis Enteropathica mutations in the extracellular domain account for mistrafficking and malfunction of ZIP4

Abstract: ZIP4 is a representative member of the Zrt-/Irt-like protein (ZIP) transporter family and responsible for zinc uptake from diet. Loss-of-function mutations of human ZIP4 (hZIP4) drastically reduce zinc absorption, causing a life-threatening autosomal recessive disorder, Acrodermatitis Enteropathica (AE). Although the zinc transport machinery is located in the transmembrane domain conserved in the entire ZIP family, half of the missense mutations occur in the extracellular domain (ECD) of hZIP4, which is only p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…In contrast, ZNT proteins decrease intracellular Zn levels by promoting Zn release from the cell or its uptake into intracellular vesicles. The sequestration of Zn is primarily controlled by Zn-dependent mechanisms that regulate the transcription, translation, and intracellular trafficking of these transporters [ 100 ]. Indeed, many studies show that the expression levels of Zn transporters in plant tumors have been found to correlate with the severity of malignancy, indicating that disruptions in intracellular Zn homeostasis can contribute to cancer progression.…”
Section: Role Of Metals In Insectsmentioning
confidence: 99%
“…In contrast, ZNT proteins decrease intracellular Zn levels by promoting Zn release from the cell or its uptake into intracellular vesicles. The sequestration of Zn is primarily controlled by Zn-dependent mechanisms that regulate the transcription, translation, and intracellular trafficking of these transporters [ 100 ]. Indeed, many studies show that the expression levels of Zn transporters in plant tumors have been found to correlate with the severity of malignancy, indicating that disruptions in intracellular Zn homeostasis can contribute to cancer progression.…”
Section: Role Of Metals In Insectsmentioning
confidence: 99%